Pooled Analysis of Risk Stratification of Spontaneous Type 1 Brugada ECG: Focus on the Influence of Gender and EPS - Li, Xinye; Sacher, Frédéric; Kusano, Kengo F.; Barajas-Martinez, Hector; Liu, Nian; Li, Yanda; Gao, Yonghong; Liu, Tong; Shang, Hongcai; Antzelevitch, Charles; Hu, Dan; Xing, Yanwei (Frontiers in Physiology, 2019)
Aims: Risk stratification of patients with Brugada syndrome (BrS) is vital for accurate prognosis and therapeutic decisions. Spontaneous Type 1 ST segment elevation is generally considered to be an independent risk factor for arrhythmic events. Other risk factors include gender, syncope, sudden cardiac arrest (SCA) and positive electrophysiological study (EPS). However, the further risk stratification of of spontaneous type 1 combined with the other risk factors remains unclear. The present study pooled data from 4 large trials aiming to systematically evaluate the risk of spontaneous Type-1 ECG when combined with one or more of these other recognized risk factors. Methods: We searched for related studies published from November 2, 2002 to February 10, 2018 in PubMed, EMBASE, Cochrane Library, MEDLINE, Chinese National Knowledge Infrastructure (CNKI) and Wanfang Databases. The pooled data were evaluated combining each risk factor with the presence of a spontaneous Type-1 ECG. All analyses were performed using Review Manager, version 5.0.12. Results: Four eligible studies involving 1,338 patients (85% males, mean age: 48.1± 18.1 years) were enrolled. Spontaneous Type-1 ECG, was associated with higher risk for ventricular tachycardia/fibrillation (VT/VF) than cases with non-Type 1 ECG in males (odds ratio: 95% CI: 1.84–5.17; P<0.0001), but not in females (P=0.29). Among spontaneous Type-1 cases with syncope or with positive EPS, the difference was not statistically significant (P=0.06 and 0.07, respectively). Patients with Type-1 ECGs and positive EPS were at higher risk than those with negative EPS (95% CI: 1.10-5.04; P=0.03). Pooled analysis showed an association of Spontaneous Type-1 ECG, Type-1 ECGs combined with male, and Type-1 ECGs combined with positive EPS between increased risk of arrhythmic events. Conclusion: Our results indicate that in BrS patients, a spontaneous Type-1 ECG is an independent risk factor for SCD in males, but not in females. The less number of female patients remains the limitation of Brugada research. A spontaneous Type-1 BrS is associated with a worse prognosis when combined with positive EPS. This analysis is helpful for further clinical risk stratification of BrS.